A Study on Passages to Global Climate Change Financing:Funding for a Greener Earth - Joshi, Kapil Kumar (Indian Forester, 2016)
This paper provides an insight of the present global climate change financing scenario. It develops an understanding of international climate change financing architecture in relation to the various funding mechanism and institutions available at international as well as at nation levels. Contributions by such schemes at global level are discussed at one hand while as India's specific requirements for mitigation and adaptation financing in relation to National Action Plan on Climate Change (NAPCC) is highlighted on the other. Appropriateness of various multilateral and bilateral funding mechanisms for Indian forestry sector with reference to REDD+ is one of the major derivable of the study. Adequacy of such finances to meet various adaptation and mitigation activities, critical nature of funds as being an ODA rather being additionality and the future course of action of UNFCCC are some other vital issues which are fundamentally presented in the paper to make a reader perceptive as well as sensitiveabout the issue.